Laboratory and clinical teaching experience of nursing professors in the COVID-19 pandemic era: Now and the future - Choi, Seung-Yi; Jin, Songxian; Kim, Jung-Hee (Frontiers in Public Health, 2022)
Nursing professors must constantly interact with students, maintain a high level of professional performance, and meet targets and deadlines, even during a pandemic. Considering the changing educational environment, it is essential to identify contemporary limitations and problems to provide feedback for improvement. This study aimed to explore the laboratory and clinical teaching experiences of nursing professors during the COVID-19 pandemic. Focus group interviews were conducted with professors from the nursing departments of universities in Korea. In total, 19 professors who had a laboratory and clinical experience participated in this study. The collected data were analyzed using thematic analysis. The analysis identified four themes. The themes included feeling helpless in the infection management system, uncertainty about the effectiveness of alternative practice training, acceptance of changes, and preparation for future practice training. As the necessity and possibility of non-face-to-face education have been confirmed by the pandemic, it is expected that classes using technology will be actively developed in nursing practice education. The roles and attitudes of teachers and educational institutions also need to change. Nursing professors should reflect upon and evaluate challenges to prepare for post-pandemic practical education.